Growth and characterization of CuInTe2, thin films: Review - Ho, Soon Min (Medwell Publishing, 2017)
Thin films such as copper indium ditelluride could be used as absorber in low cost solar cell technology. In this study, synthesis and characterization of CuInTe2 films will be discussed, analyzed and reported. EDAX spectra show that close to ideal stoichiometric (CuInTe2) compound. XRD data supported that the formation of tetragonal structure. Optical properties reveal that band gap values range from 0.9-1.4 eV.